The Rise of Democracy Revolution, War and Transformations in International Politics since 1776 - Hobson, Christopher (Edinburgh University Press, 2015)
Little over 200 years ago, a quarter of a century of warfare with an 'outlaw state' brought the great powers of Europe to their knees. That state was the revolutionary democracy of France. Since then, there has been a remarkable transformation in the way democracy is understood and valued - today, it is the non-democractic states that are seen as rogue regimes. Now, Christopher Hobson explores democracy's remarkable rise from obscurity to centre stage in contemporary international relations.